Entrepreneurial Orientation and Firm Performance among Automotive Parts Retail Firms in Zimbabwe: The Roles of Innovation Capability and Market Turbulence - Dominic Sadaraki; Muthia Pramesti (Publikasi Indonesia, 2026)
Firms in Zimbabwe’s automotive parts retail sector operate in a dynamic market and volatile economy that threaten business competitiveness and hinder firm growth. This study aimed to investigate how entrepreneurial orientation influences firm performance among automotive parts retail firms within the broader Micro, Small, and Medium Enterprises (MSMEs) in Harare, Zimbabwe, while considering the roles of innovation capability and market turbulence. Grounded in the Resource-Based View, Dynamic Capabilities Theory, and Contingency Theory, the study employed a quantitative cross-sectional design, with data collected using an online structured and self-administered questionnaire from 204 owners and managers who had at least three years of experience in business. Data were obtained through a purposive sampling technique and analysed using the Statistical Package for the Social Sciences (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicated that entrepreneurial orientation had a positive and significant effect on firm performance and innovation capability. The relationship between entrepreneurial orientation and firm performance is partially mediated by innovation capability and negatively moderated by market turbulence. The study extends entrepreneurship literature in an under-researched context in Sub-Saharan Africa and provides insight for managers and policymakers seeking to enhance business performance. The cross-sectional design and single-sector focus may limit causal inference and generalizability.